Field notes contributed by Peter Ernzen, fall 1992 - Ernzen, Peteret al (1992)
Fall report of birds found in western Iowa contributed by Peter Ernzen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1992. Plustek - flatbed